Karakteristik Penderita Kanker Sistem Reproduksi Dan Payudara Di Laboratorium Rumah Sakit Umum Madani Periode 2019-2024 - Sintya, Inda Dhea; Lina, Juliana; Lister , Clarissa (Syntax Corporation, 2025)
Objective: To determine the general characteristics of reproductive and breast cancer patients at the Madani General Hospital Laboratory from 2019 to 2024. Method: This study used a descriptive correlational approach. The research began in December 2024 with proposal writing, followed by research in February 2025 until data collection, which was then followed by a results seminar. The accessible population consisted of all medical records of reproductive and breast cancer patients at the Madani General Hospital Laboratory, a sample size of 32, using a purposive sampling technique. Univariate data analysis was presented in the form of frequency distributions, while bivariate analysis used the chi-square test. Data processing was performed using the computerized IBM SPSS version 25.0. Results: The highest number was in the age group of 52-56 years, totaling 8 people (25%), almost half of the respondents had an origin organ of endometrium and breast, totaling 12 people (41.4%), and almost half of the respondents had of the respodents had a diagnosis of endometrial adenocarcinoma. There was a correlation between organ origin and diagnosis in patients with reproductive system and breast cancer at the Madani General Hospital Laboratory during the 2019-2024 period (p=0.000). There was no correlation between age and diagnosis in patients with reproductive system and breast cancer at the Madani General Hospital Laboratory during the 2019-2024 period (p=0.097). Conclusion: There was a correlation between origin organ and diagnosis, but no correlation between age and diagnosis in patients with reproductive system and breast cancer at the Madani General Hospital Laboratory during the 2019-2024 period.